The ruses of war - Quigley, John. ([S.l.] : Pentagon Press, 2007)
Why were Americans troops committed to Korea in 1950? Was it to stop the onslaught of world communism, as President Truman claimed? Why did the US marines land the Domnican republic in 1966? President Johnson argues that it was to protect Americans in danger...etc.